2014
DOI: 10.1111/jdv.12395
|View full text |Cite
|
Sign up to set email alerts
|

Observational study on the mitotic rate and other prognostic factors in cutaneous primary melanoma arising from naevi and from melanoma de novo

Abstract: When mitosis ≥ 1 mm/mm(2) , the results obtained do not show a better or worse prognosis based on Breslow's thickness, ulceration and MR in melanomas associated with naevus vs. melanomas de novo. When ≥6 mitosis/mm(2) are considered, the number of patients in the de novo melanoma group with thick melanoma is highly more represented. The debate about the cut-off value of mitosis ≥1 mm(2) is open.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This study also found that nevus-associated melanomas were more likely to be associated with thinner tumors, and thus had a better prognosis in general. Although some previous studies have reported that Breslow thickness did not differ significantly in nevus-associated versus de novo melanomas, thinner tumors have been found to be associated with an increased likelihood of nevus-associated melanoma in other reports [6, 11, 12, 24, 2629]. More specifically, nevus-associated melanomas were reported to be more frequent in thinner tumors, possibly owing to the obliteration of nevocytic remnants in more advanced melanomas [12, 24].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This study also found that nevus-associated melanomas were more likely to be associated with thinner tumors, and thus had a better prognosis in general. Although some previous studies have reported that Breslow thickness did not differ significantly in nevus-associated versus de novo melanomas, thinner tumors have been found to be associated with an increased likelihood of nevus-associated melanoma in other reports [6, 11, 12, 24, 2629]. More specifically, nevus-associated melanomas were reported to be more frequent in thinner tumors, possibly owing to the obliteration of nevocytic remnants in more advanced melanomas [12, 24].…”
Section: Discussionmentioning
confidence: 85%
“…The histologic melanoma subtypes were classified as ALMs, SSMs, NMs, LMMs, mucosal melanomas, and desmoplastic melanomas. According to a recent study [11], the mitotic count was categorized into groups of <1 mitosis/mm 2 , 1–5 mitoses/mm 2 , and ≥ 6 mitoses/mm 2 . Lesions distributed on the trunk and extremities were acknowledged to be distributed on areas receiving intermittent sun exposure; lesions on the head and neck were regarded as being located on areas receiving chronic sun exposure; and the acral and genital areas were recognized as non-sun-exposed areas [12].…”
Section: Methodsmentioning
confidence: 99%
“…A recent review demonstrated that a single mitosis in thin melanomas did not increase the risk of sentinel lymph node positivity, although it was related to a significant decrease in survival rate [ 33 ]. A retrospective study comparing de novo melanomas and nevus-associated melanomas found that there are no prognostic differences when the mitotic rate is considered for one or more mitoses; however, there are prognostic differences when this criterion is considered for more than five mitoses, which raises the question of what should be the cut-off point for this variable [ 34 ]. Indeed, as discussed in [ 14 ], incorporating the MR into the staging system has proven difficult given the nonlinear nature of its impact on survival.…”
Section: Discussionmentioning
confidence: 99%
“…The independent prognostic value of the mitotic rate has been described in various studies [ 7 , 29 , 38 , 39 , 40 , 41 ]. Despite these results, there is still no consensus regarding the prognostic cut-off value for the number of mitoses as different studies have used various thresholds, such as absent vs. present, ≥1/mm 2 , ≥2/mm 2 , or 5 mitoses/mm 2 [ 1 , 42 , 43 , 44 , 45 ]. Moreover, the significant cut-off values may vary based on the tumor stage, and further studies are required to fully establish how the mitotic index should be reported in cutaneous melanomas [ 7 , 40 , 46 ].…”
Section: Discussionmentioning
confidence: 99%